2016
DOI: 10.5501/wjv.v5.i3.125
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and pathotyping of diversified strains of infectious bronchitis viruses circulating in Egypt

Abstract: These findings indicated that the recent circulating Egyptian IBVs have multiple heterogeneous origins in marked diversifying nature of their spread, with high pathotype in specific pathogen free chicks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
8
35
1
Order By: Relevance
“…The symptoms observed in the case report are consistent with those described in former outbreaks in Egypt, Turkey, and Poland (Yilmaz et al, 2016;Zanaty et al, 2016;Lisowska et al, 2017). Birds showed respiratory as well as nephropathogenic symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The symptoms observed in the case report are consistent with those described in former outbreaks in Egypt, Turkey, and Poland (Yilmaz et al, 2016;Zanaty et al, 2016;Lisowska et al, 2017). Birds showed respiratory as well as nephropathogenic symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…occurred between polish GI-23 IBV strains and German field or vaccine strains (Zanaty et al, 2016). This hypothesis has to be proved in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…The results revealed that these viruses were separated into two distinct groups; variant (variant 2) and classic. Meanwhile Zanaty et al [27] isolated 20 IBV viruses, 16 belonged to variant group and 4 belonged to classic group (Mass-like). The variant group was subdivided into 6 isolates (Egy /Var-1) and 10 isolates (Egy /Var -2).…”
Section: Discussionmentioning
confidence: 99%
“…Each dot represents the mean of the clinical signs scoring of all birds in the group at each time point. 34]. Despite wide spread vaccination with classical and/or variant strain based vaccines in Egypt, IBV outbreaks were frequently reported in vaccinated and non-vaccinated flocks of farms [16], indicating poor protection against the prevalent local variant strain [35].…”
Section: Discussionmentioning
confidence: 99%